Supramolecular Nanofibers as Ambient Stable Wide Voltage Window Electrolyte for Micro‐Supercapacitors. Issue 1 (21st December 2016) - Mogera, Umesha; Gedda, Murali; George, Subi J.; Kulkarni, Giridhar U.
Abstract: In this paper, we explore the use of supramolecular nanofibers as an electrolyte for in‐plane micro‐supercapacitors. The supramolecular nanofibers obtained from the self‐assembly of donor–acceptor (D‐A) molecules, coronene tetracarboxylate salt (CS) and dodecyl methyl viologen (DMV), carrying positive and negative ionic charges, respectively, were drop‐coated onto metal gap electrodes using an aqueous dispersion to form the device. Under dry conditions (<35 % relative humidity, RH), the device exhibited a stack capacitance of 160 F cm −3 with energy and power densities comparable to high‐performance micro‐supercapacitors. Although the electrolyte has aqueous origin, in dry conditions, it is capable of operating in a voltage window of 0–3 V. This supramolecular micro‐supercapacitor device (micro‐SS) was fabricated only with metal electrodes without using electrode material in it, thanks to the ability of the nanofiber to provide extended surface area for charge storage. The 1D face‐to‐face arrangement of D‐A molecules seems to provide an efficient pathway for the diffusion of ions across the electrodes. The present study not only provides a new approach to obtain an ambient stable electrolyte with wide operating voltage window but also gives a low‐cost method of fabricating micro‐supercapacitors with reasonably high energy and power densities. Abstract : Open the window : Supramolecular nanofibers are shown to be an ambient stable electrolyte material like aqueous electrolytes while offering, like non‐aqueous electrolytes, a wider voltage window operation in supercapacitors.